Quelques considérations sur le droit linguistique - Turi, Joseph-G. (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
The law of languages truly is new ground for legal thinking and even may be considered futuristic in as much as it is law that recognizes differences among men. In this respect, the Loi sur la langue officielle and the Charte de la langue française of Québec confirm the right to specific linguistic expression in the form of acts that are territorially and materially exhaustive — these laws are outstanding examples for anyone who is interested in comparative law of languages. Nonetheless, the law of languages profoundly touches upon concepts that are of capital social importance : culture, minority language rights and fundamental freedoms. Furthermore, the very object of linguistic legislation which of course is language, is per se an object that hardly lands itself to appropriation either linguistically or legally — and as a basic means for expressing legal thought, language simultanously is the subject and object of law dealing with meta-legal and meta-linguistic concepts. Lastly, there exist in Québec important restrictions of both a structural and operative nature that relate to the interpretation and enforcement of Quebec law on language usage. This is why the legal impact of language laws, in general, and Quebec law, in particular, is of minor importance, whereas the cultural impact is of major concern.